Water quality of Angke River: Microbiological point of view (Medical Journal of Indonesia, 2008)
This research is a part of a multidisciplinary research in the Angke River. The aim of this research is to study the river's water quality from the microbiological point of view in several locations along the Angke River. The locations under this study included: Duri Kosambi, Pesing Poglar, Teluk Gong, Pantai Indah Kapuk and Estuary (4 points). The examinations were held in term of microbiological aspects, based on the guide published by the Ministry of Health, the Republic of Indonesia and concluded according to Government Regulation. The parameter of microbiological tests was the most probability number (MPN) of total and fecal coliform. The method used was done in 2 steps: presumptive and confirmed test. Completed test was conducted to confirm the presence of E.coli and other bacteria in water. The result showed that the water quality of the Angke River was poor; therefore, it is not recommended to be used as drinking water. It is categorized as the 2nd class quality that means it can only be used for water recreation, veterinary, showering plants and or other purposes that require the same quality of water. The MPN of total coliform at Pantai Indah Kapuk and the outer side of river mouth (estuary area) was lower than other areas. People who live in Pantai Indah Kapuk are having a higher economic level. Therefore, it can be assumed that they are more educated people who have more insight about hygiene. Further, the water at the outer side of river mouth contains a higher salt concentration that can kill pathogenic bacteria. In conclusion, the water quality of the Angke River is categorized as 2nd class quality not recommended to be used as dringking water except the water from Pantai Indah Kapuk and estuary area that can be used as dringking water after boiling. (Med J Indones 2008; 17:82-7)